Bird species co‐occurrence patterns in an alpine environment supports the stress‐gradient hypothesis. Issue 11 (12th October 2021) - García‐Navas, Vicente; Sattler, Thomas; Schmid, Hans; Ozgul, Arpat
Abstract : Understanding the relative contribution of different biotic interactions in shaping species assemblages constitutes a major goal in community ecology, and consequently, multiple methods aimed at inferring the nature of these associations have emerged during the last decade. In this framework, the stress‐gradient hypothesis (SGH) predicts that prevalent biotic interactions shift from competition to facilitation as abiotic stress increases (and productivity decreases). This hypothesis originally raised by plant ecologists has been barely applied to faunal communities. Here, we take advantage of 20 years of abundance data to investigate pairwise patterns in species co‐occurrence in alpine bird communities inhabiting two contrasting habitat types: forests (high productivity) and mountain grasslands (low productivity). We also integrate functional data with presence–absence and quantitative matrices in order to detect the signature of processes driving community assembly and test for limiting similarity. We employ a null model approach, probabilistic pairwise association tests and joint species distribution models; all methods revealed a higher frequency of positive interactions in mountain grasslands in agreement with SGH predictions. Both the frequency of positive and negative interactions remained moderately stable over the study period in both habitat types. There was no significant relationship between the degree of co‐occurrence of species pairs and their functional distance in either habitat. However, when we only considered those combinations of species whose co‐occurrence patterns deviated from that expected at random, we found that co‐existing species are functionally more similar than those pairs that show segregated patterns in the forest assemblages. Such a relationship may arise via selective social information use and other processes, including microhabitat preferences. Overall, our findings suggest that interspecific competition does not constitute a major force driving the structure of bird assemblages in this mountain region. This work also shows that association analyses should not be underestimated as they can provide clues to the mechanisms responsible for community structure.